2013
DOI: 10.1089/ten.tea.2012.0073
|View full text |Cite
|
Sign up to set email alerts
|

In VivoBioluminescence Imaging of Cell Differentiation in Biomaterials: A Platform for Scaffold Development

Abstract: In vivo testing is a mandatory last step in scaffold development. Agile longitudinal noninvasive real-time monitoring of stem cell behavior in biomaterials implanted in live animals should facilitate the development of scaffolds for tissue engineering. We report on a noninvasive bioluminescence imaging (BLI) procedure for simultaneous monitoring of changes in the expression of multiple genes to evaluate scaffold performance in vivo. Adipose tissue-derived stromal mensenchymal cells were dually labeled with Ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…Reprinted with permission from Chen et al 93 (C) In vivo monitoring of human adipose tissuederived stromal mesenchymal cell differentiation in subcutaneous implanted demineralized bone matrix scaffolds using bioluminescence imaging. Reprinted with permission from Bago et al 104 Color images available online at www.liebertpub.com/teb constructs are enabled with the penetration depth increased up to *500 mm. 59,82 For instance, two-photon fluorescence microscopy has been successfully applied to visualize the structure of polymer gels and engineered tissue at different depths, even in a bioreactor system (Fig.…”
Section: Optical Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Reprinted with permission from Chen et al 93 (C) In vivo monitoring of human adipose tissuederived stromal mesenchymal cell differentiation in subcutaneous implanted demineralized bone matrix scaffolds using bioluminescence imaging. Reprinted with permission from Bago et al 104 Color images available online at www.liebertpub.com/teb constructs are enabled with the penetration depth increased up to *500 mm. 59,82 For instance, two-photon fluorescence microscopy has been successfully applied to visualize the structure of polymer gels and engineered tissue at different depths, even in a bioreactor system (Fig.…”
Section: Optical Imagingmentioning
confidence: 99%
“…7C). 104,105 However, in spite of the advantages of bioluminescence imaging, this technique is not appropriate for studies requiring high spatial resolution (better than millimeter level), quantitative analysis, and accurate 3D reconstruction. In addition, bioluminescence imaging is not applicable for clinical applications because of safety issues for bioluminescent reporter genes.…”
Section: Optical Imagingmentioning
confidence: 99%
“…34, 79, 90, 113 Through reporter design with specific osteogenic or chondrogenic markers and dual bioluminescence labeling, cell differentiation through the changes in gene expression patterns can also be elucidated. 11, 119 A detailed discussion of BLI transgenic reporters and potential applications specifically for bone tissue engineering can be found in other reviews. 33 …”
Section: In Vivo Characterization Of Biomaterials For Bone and Cmentioning
confidence: 99%
“…Several studies that have demonstrated the feasibility of using BLI to track delivered cells for several weeks following implantation have also observed the development of various tissue types (including vascular, fibrotic, and mineralized) within constructs over the associated time-course. 1,[13][14][15][16][17] Thus, the impact of this tissue invasion on the accuracy of BLI measurement remains unclear.…”
Section: Introductionmentioning
confidence: 99%